2016
DOI: 10.1021/acsami.5b11582
|View full text |Cite
|
Sign up to set email alerts
|

Direct Cross-Linking of Au/Ag Alloy Nanoparticles into Monolithic Aerogels for Application in Surface-Enhanced Raman Scattering

Abstract: The direct cross-linking of Au/Ag alloy nanoparticles (NPs) into high surface area, mesoporous Au/Ag aerogels via chemical oxidation of the surface ligands is reported. The precursor alloy NPs with composition-tunable morphologies were produced by galvanic replacement of the preformed Ag hollow NPs. The effect of Au:Ag molar ratio on the NP morphology and surface plasmon resonance has been thoroughly investigated and resulted in smaller Au/Ag alloy NPs (4-8 nm), larger Au/Ag alloy hollow NPs (40-45 nm), and Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 69 publications
1
50
0
4
Order By: Relevance
“…[103] Pure Ag nanoshells could be assembled into opaque and transparent gels by first concentrating the colloid followed by the oxidation of the surface ligands.T he etching of the nanoshells into significantly smaller nanoparticles is responsible for the formation of the transparent gels. [105] A20-fold increase in SERS intensity was achieved in the final gels compared to the initial nanoparticles. [105] A20-fold increase in SERS intensity was achieved in the final gels compared to the initial nanoparticles.…”
Section: Galvanic Replacement As Asynthesis Toolmentioning
confidence: 90%
See 1 more Smart Citation
“…[103] Pure Ag nanoshells could be assembled into opaque and transparent gels by first concentrating the colloid followed by the oxidation of the surface ligands.T he etching of the nanoshells into significantly smaller nanoparticles is responsible for the formation of the transparent gels. [105] A20-fold increase in SERS intensity was achieved in the final gels compared to the initial nanoparticles. [105] A20-fold increase in SERS intensity was achieved in the final gels compared to the initial nanoparticles.…”
Section: Galvanic Replacement As Asynthesis Toolmentioning
confidence: 90%
“…[102][103][104][105] Thei nitial nanoshells are produced via ag alvanic replacement reaction of pre-formed Ag and Ni nanoparticles,respectively.Au/Ag, Pd/ Ag, and Pt/Ag alloyed nanoshells were first concentrated by either simple solvent evaporation or with the help of centrifuge membrane filters.Colloidal solutions concentrated through solvent evaporation spontaneously formed ag el when stored in the dark for several days,w hereas the nanoshell solution concentrated with centrifuge filters could be destabilized by the addition of NaCl. [102][103][104][105] Thei nitial nanoshells are produced via ag alvanic replacement reaction of pre-formed Ag and Ni nanoparticles,respectively.Au/Ag, Pd/ Ag, and Pt/Ag alloyed nanoshells were first concentrated by either simple solvent evaporation or with the help of centrifuge membrane filters.Colloidal solutions concentrated through solvent evaporation spontaneously formed ag el when stored in the dark for several days,w hereas the nanoshell solution concentrated with centrifuge filters could be destabilized by the addition of NaCl.…”
Section: Galvanic Replacement As Asynthesis Toolmentioning
confidence: 99%
“…Impressively, an ultrahigh specific surface area of up to 160 m 2 g −1 was obtained for the resulting Ag–nanoshell‐based aerogels, outperforming the SSAs of most NMFs. Several following studies further expanded the system to Au–Ag and Au–Ag–Pd aerogels . By engineering the composition of ternary Au–Ag–Pd alloy NPs by the stepwise galvanic replacement reaction (GRR) of l ‐glutathione‐stabilized Ag NPs, Nahar et al observed that spherical and anisotropic NPs were obtained with higher and lower Pd proportion, respectively, further resulting in gels with different microstructures.…”
Section: Fabrication Strategiesmentioning
confidence: 99%
“…[102][103][104][105] Die ursprünglichen Nanoschalen werden mithilfe galvanischer Austauschreaktion aus Ag-oder Ni-Nanopartikeln hergestellt. [102][103][104][105] Die ursprünglichen Nanoschalen werden mithilfe galvanischer Austauschreaktion aus Ag-oder Ni-Nanopartikeln hergestellt.…”
Section: Galvanischer Austausch Als Synthesehilfsmittelunclassified
“…[105] Gegenüber den Ausgangsnanopartikeln wurde in den fertigen Gelen ein 20-facher Anstieg in der SERS-Intensitäterreicht. [105] Gegenüber den Ausgangsnanopartikeln wurde in den fertigen Gelen ein 20-facher Anstieg in der SERS-Intensitäterreicht.…”
Section: Angewandte Chemieunclassified